Influence of the pH and Salt Concentrations on Physicochemical Properties of Pork Myofibrillar Protein Gels Added with Cornstarch - Lee, Chang Hoon (Food Sci Anim Resour, 2020)
The aim of this study was to evaluate quality characteristics of pork myofibrillar protein (MP) added with cornstarch as affected by different pH values and salt cocnentrations. MP mixtures were prepared with three different pH values (pH 6.00, 6.25, and 6.50) and three different salt concentrations (0.15, 0.30, and 0.45 M). Cooking yield (CY), gel strength, viscosity, and scanning electron microscopy were measured to evaluate characteristics of MPs. CYs of MPs with cornstarch at above pH 6.25 or salt 0.30 M were increased compared to those at pH 6.00 or salt 0.15 M. However, gel strengths of MPs at salt 0.45 M were higher than those at salt 0.30 M. In microstructure analysis, MP gels with increasing pH value and salt concentration showed compact and uniform structure. Thus, MP gels with pH 6.25 and salt concentration of 0.30 M would be better for manufacturing meat products containing cornstarch to increase their water holding ability.